Team-based learning in the social science and humanities [ group work that works to generate critical thinking and engagement - Michaelsen, Larry K. , 1943-; Sweet, Michael (Stylus Publishing, 2012)
Team-Based Learning (TBL) is a unique, powerful, and proven form of small-group learning that is being increasingly adopted in higher education to achieve high levels of student engagement, critical thinking, and retention. TBL has been used successfully in both small and large classes, in computer-supported and online classes, in nearly every discipline, and in countries around the world. This book introduces the practical elements of TBL and how to apply them in the social sciences and humanities, paying particular attention to the specification of learning goals, which can be a unique challenge in our fields. The core of the book consists of examples of how TBL has been incorporated into the cultures of disciplines as varied as economics, education, literature, politics, psychology, and theatre. At a time of increasing course sizes, and emphasis on learning outcomes, TBL offers the means to meet such demands while helping students learn course content in deeper and more accessible ways than they have in the past.